A web-based library search engine using conflation method / Zulfahanan Abdul Gani - Abdul Gani, Zulfahanan (2010)
Information retrieval (IR) is a field that helps a lot in searching process, so that is why it is used widely nowadays in many applications, systems and so on. With the development of the World Wide Web, the information search has grown to be a significant business sector of a global, competitive and commercial market. Many methods are used in order to make a powerful search engine including by using Stemming Algorithm which are in Conflation Method. Library system also needs to be grown with powerful search engine that can give an effective search ways to the users. As we know, library system is centre of information to the users and it must provide better search engine in order to ease user to get any information from it. Nowadays, there are many library search engine that are created, but usually for high institution like for university and just for some schools only. Therefore, first objective of this project is to develop a data collection for library search engine. Second, to design and develop library search engine for students using Conflation Method. In this project also, indexing technique where inverted index file is used in order to speed up searching. Actually, indexing is a data structure build on the text.